Fear of Abandonment and Psychosomatic Symptoms: The Mediating Role of Attachment Insecurity - Lai , Wang (Journal of Personality and Psychosomatic Research (JPPR), 2025)
This study aimed to examine the relationship between fear of abandonment and psychosomatic symptoms and to investigate whether attachment insecurity mediates this relationship in a sample of Chinese young adults. The research followed a descriptive correlational design and included 419 participants from urban areas in China, selected based on the Morgan and Krejcie sampling table. Standardized instruments were used to measure fear of abandonment (Fear of Abandonment Scale), attachment insecurity (Experiences in Close Relationships–Revised), and psychosomatic symptoms (PHQ-15). Data were analyzed using Pearson correlation coefficients in SPSS-27 and structural equation modeling (SEM) in AMOS-21 to assess the mediating role of attachment insecurity. The results showed that fear of abandonment was positively correlated with both attachment insecurity (r = .62, p < .001) and psychosomatic symptoms (r = .51, p < .001). Attachment insecurity also had a significant positive correlation with psychosomatic symptoms (r = .57, p < .001). The structural model demonstrated good fit indices (χ²/df = 2.13, CFI = .96, RMSEA = .052), confirming the adequacy of the hypothesized model. Path analysis revealed that fear of abandonment significantly predicted attachment insecurity (β = .62, p < .001), which in turn predicted psychosomatic symptoms (β = .46, p < .001). The direct effect of fear of abandonment on psychosomatic symptoms remained significant (β = .22, p = .002), and the indirect effect through attachment insecurity was also significant (β = .29, p < .001), indicating partial mediation. These findings suggest that fear of abandonment contributes to psychosomatic symptoms both directly and indirectly through its impact on attachment insecurity. Addressing attachment-based vulnerabilities may be essential in the psychological treatment of individuals experiencing psychosomatic distress.